مركز التعليم البيئي والبحث - رغد مسلماني (My University, 2025)
The “Environmental Research Center with an Educational Identity” is an architectural project that seeks to strengthen the relationship between humans and the environment by providing an integrated space for scientific research, awareness, and education. The design is rooted in sustainability and natural integration with the site’s topography, adopting an organic architectural language inspired by natural elements such as plant forms and land patterns. The project consists of two main components: • The solid mass: This includes specialized laboratories for plant science, water, soil, and renewable energy, along with flexible educational spaces equipped for workshops, exhibitions, and environmental learning activities. • The glazed structure: A closed botanical garden that forms the heart of the project, acting as a visual and experiential core that encourages sensory interaction with plant biodiversity. Functional spaces are distributed to ensure a balance between privacy and openness, supporting intuitive movement through different areas while maximizing natural light and ventilation. The center incorporates sustainable systems such as rainwater harvesting, solar energy utilization, and natural shading strategies. The project emphasizes learning through experience, serving university and school students, researchers, and environmentally conscious visitors. It aims to be a dynamic educational and cultural hub that raises environmental awareness and highlights the human role in ecological sustainability.